2022
DOI: 10.3389/fphar.2022.837907
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Traditional Chinese Medicine and its Active Ingredients on Drug-Resistant Bacteria

Abstract: The increasing and widespread application of antibacterial drugs makes antibiotic resistance a prominent and growing concern in clinical practice. The emergence of multidrug-resistant bacteria presents a global threat. However, the development and use of novel antibacterial agents involves time-consuming and costly challenges that may lead to yet further drug resistance. More recently, researchers have turned to traditional Chinese medicine to stem the rise of antibiotic resistance in pathogens. Many studies h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 119 publications
0
14
0
Order By: Relevance
“…Some traditional Chinese medicines have good abilities of bacteriostasis for bacteria, including foodborne bacteria [23]. C. chinensis, S. chinensis, and honeysuckle are frequently applied in the treatment of the infection of bacteria [24][25][26].…”
Section: Application On the Study Of Bacteriostasis By Traditional Ch...mentioning
confidence: 99%
“…Some traditional Chinese medicines have good abilities of bacteriostasis for bacteria, including foodborne bacteria [23]. C. chinensis, S. chinensis, and honeysuckle are frequently applied in the treatment of the infection of bacteria [24][25][26].…”
Section: Application On the Study Of Bacteriostasis By Traditional Ch...mentioning
confidence: 99%
“…Many studies have demonstrated that traditional Chinese medicine (TCM) contains a diverse range of active components including antibacterial activity with the advantage of low drug resistance. 14,15 Our previous study proved that Patrinia scabiosaefolia possessed strong antibacterial against methicillin resistant Staphylococcus epidermidis. 16 Similarly, Houttuynia cordata showed good antibacterial activity to Staphylococcus aureus.…”
Section: Introductionmentioning
confidence: 99%
“…Research into antibiotic resistance is now gradually attracting widespread attention. Chinese traditional medicine (TCM) plays a unique role in regulating the activity of drug-resistant bacteria ( Su et al., 2020 ; Li et al., 2022 ), including altering the permeability of the biofilm of drug-resistant bacteria, the efflux pump, and the occurrence of resistance mechanisms such as enzyme activity. In addition, most TCMs are taken orally into the digestive tract to exert their regulatory effects on the body, while some studies have found that changes in the gut microbiota and gut microenvironment affect pathogenic bacteria in the gut ( Baumler and Sperandio, 2016 ).…”
Section: Introductionmentioning
confidence: 99%